Single-Molecule Sensing of Biomolecular Interactions on DNA Nanostructures - Zhang, Ting; Collins, John; Fu, Jinglin (Current Nanoscience, 2015)
Living systems have evolved a variety of complex nanostructures to control biomolecular interactions and biochemical reactions that are vital to the metabolism and reproduction. During the past few decades, single-molecule detection and imaging have been widely applied to interpreting biological processes in detail, which are able to observe the chemical reactions and kinetic behaviors of individual molecules. The rapid development of structural DNA nanotechnology has provided adaptable platforms to facilitate single-molecule detection and super-resolution imaging of individual biological components, as well as manipulating artificial nanosystems with molecular precision. In this review, we summarize recent exciting progress in using DNA nanostructures to sense and manipulate biomolecular interactions at the single-molecule level.
Keywords: nanorobots